The incidence, prevalence, severity, mechanism and body region of injury in elite junior Australian football players: A prospective cohort study over one season - Lathlean, T. J. H.; Gastin, P. B.; Newstead, S. V.; Finch, C. F. (Journal of Science and Medicine in Sport, 2018)
Objectives: To describe the incidence, prevalence, severity, mechanism and body region of injuries in elite junior Australian football (AF) players over one competitive season in order to help inform injury prevention interventions. Design: Prospective cohort, data collected during the 2014 playing season. Methods: Player and staff-reported injuries sustained by 562 players from an under-18 state league were entered into an online sports injury surveillance system. An injury was recorded if it led to a missed training session or match. Injury incidence was calculated as the number of injuries per 1000 h of training and competition. Injury severity was defined by the number of days players missed training or competition. Injury mechanism was identified as either contact, non-contact or overuse. Results: There were 1192 football-related injuries sustained during the season; the majority (n = 1041, 87.3%) were new, occurred during competition (n = 954, 86%) and led to 4-7 missed days in severity (n = 429, 46%). Injury incidence was 37.2 injuries per 1000 h of exposure. Over half of injuries were contact in mechanism (n = 355, 51%). Most injuries were to the lower limb (n = 720, 60%), with the thigh representing the highest proportion of these. Conclusions: This study provides key information as to the aetiology of injury in this level of competition and provides a stronger foundation from which injury prevention studies could be carried out. Future research is well-placed to develop an understanding of the injury risk factors in the elite junior cohort, whilst also reducing injury risk once players transition to the AFL. ABSTRACT FROM AUTHOR